PENGEMBANGAN E-MODULE INTERAKTIF BERBASIS STEM UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SD NEGERI 8 BAKTIA BARAT - Herawati (Jurnal Humaniora Pendidikan (JHP), 2025)
This study aims to develop an interactive STEM-based e-module to improve elementary school students’ critical thinking skills. The low level of students’ critical thinking abilities and the dominance of conventional teaching materials highlight the need for technology-based learning innovation. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The participants included subject matter experts, media experts, classroom teachers, and 30 fourth-grade students at SD Negeri 8 Baktia Barat. The research instruments consisted of validation sheets, practicality questionnaires, critical thinking tests, and observation sheets. Data were analyzed using validity analysis, practicality analysis, N-Gain, and paired sample t-test. The results showed that the developed e-module was categorized as highly valid with an average score of 4.61, highly practical with a percentage of 90%, and effective in improving students’ critical thinking skills. This is indicated by the increase in the mean pretest score from 52.30 to 82.60 in the posttest, with an N-Gain score of 0.64 (moderate category) and a significant difference based on the t-test (p < 0.05). Therefore, the interactive STEM-based e-module is proven to be feasible and effective in enhancing elementary school students’ critical thinking skills.